Hepatic Steatosis in Infancy: The Beginning of Pediatric Nonalcoholic Fatty Liver Disease?. Issue 3 (5th August 2021) - McNelis, Kera; Yodoshi, Toshifumi; Divanovic, Senad; Gandhi, Chandrashekhar; Kim, Jae H.; Anton, Christopher G.; Trout, Andrew T.; Mouzaki, Marialena
Abstract : Objectives: Nonalcoholic fatty liver disease is clinically silent and the age of its onset is unknown. Fatty liver can occur as early as in utero in the context of an unfavorable maternal metabolic environment. Our objective was to determine the prevalence of hepatic steatosis in a cohort of previously healthy infants less than 3 months of age. Methods: Retrospective study of all abdominal computed tomography (CT) scans performed from 2009 to 2019 for the investigation of trauma. Two independent reviewers applied published criteria to determine the presence of hepatic steatosis. Descriptive statistics were used. The groups with and without steatosis were compared using Wilcoxon-Mann Whitney or Fisher exact test. Results: Of 119 CT scans available in infants younger than 3 months of age, 65 were performed in previously healthy infants for the investigation of trauma. The included population was predominantly male, non-Hispanic, with a median age of 60 days (interquartile range, 34–73 d). Depending on the criteria used, 23% or 26% of infants had evidence of fatty liver. The prevalence of maternal obesity and/or diabetes was 11% (of the 65 pregnancies) but there was no significant difference in maternal risk factors between infants with and without evidence of steatosis. Conclusions: Findings suggest CT evidence of hepatic steatosis in up to a quarter of otherwise healthy infants ≤3 months of age. This may represent early manifestation of pediatric nonalcoholic fatty liver disease. The natural history and pathophysiology of this condition need to be studied to determine optimal detection, prevention and early intervention strategies.